Ventriculoperitoneal Shunt Failures At Red Cross War Memorial Children's Hospital - Lazarus, Jed (Division of General Surgery, 2024)
Introduction Ventriculoperitoneal shunt (VP shunt) insertion is one of the mainstays of treatment of hydrocephalus and although very effective, a high rate of shunt failure persists globally. The purpose of the study was to quantify the ventriculoperitoneal shunt failure rate at Red Cross War Memorial Children's Hospital (RCWMCH) and assess potential factors contributing to shunt failures. Methods A retrospective review of VP shunts done at RCWMCH between August 2015 through December 2019 was performed. Operative notes, discharge summaries and patient folders were reviewed to collect information about patient age, aetiology of hydrocephalus, index vs revision shunt, shunt system and other noticeable variables. Overall shunt failure was recorded. Univariate and multivariate models were used to determine causal relationship. Results Four hundred and ninety-four VP shunt operations were performed on 340 patients with 48.8% being index shunts and 51.2% revision shunts. Average patient age was 3.4months. The total VP shunt failure rate over the study period was 31.2%, with a 7.3% infection rate, 13.6% blockage and 3.6% disconnection rate. The most common aetiologies were Post infectious hydrocephalus 29.4%, Myelomeningocele 19.7% and Premature Intraventricular haemorrhage 14.1%. Orbis-sigma II(OSVII), Distal slit valves and Antibiotic impregnated catheters were used most frequently. Failure rates were highest in the revision group, 34.7% compared to 27.3% in index shunts. Conclusion VP shunt failure occurs most commonly in revision surgery, and care should be taken at the index operation to reduce failure risk. Surgeon level, duration of surgery, aetiology of hydrocephalus and shunt system used did not influence overall failure rates.